Evaluation of the genetic toxicity of synthetic chemicals (XVI) - in vitro mouse lymphoma assay with 3 chemicals - Kim, Youn-Jung; Ryu, Jae-Chun (KOREAN SOC TOXICOGENOMICS & TOXICOPROTEOMICS, 2006)
The detection of many synthetic chemicals used in industry that may pose a genetic hazard in our environment is of great concern at present. Since these substances are not limited to the original products, and enter the environment, they have become widespread environmental pollutants, thus leading to a variety of chemicals that possibly threaten the public health. In this respect, to regulate and to evaluate the chemical hazard will be important to environment and human health. The genotoxicity of 3 synthetic chemicals was evaluated in L5178Y tk(+/-) mouse lymphoma cells in vitro. 9H-carbazole (CAS No. 86-74-8) did not induce significant mutation frequencies both in the presence and absence of metabolic activation system. 1, 3-Dichloro-2-propanol (CAS No. 96-23-1) revealed a significant increase of mutation frequencies in the range of 625-373 mu g/mL in the absence of metabolic activation system and 157-79 mu g/mL in the presence of metabolic activation system. And also, fenpropathrin (CAS No. 64257-84-7) appeared the positive results only in the absence of metabolic activation system. Through the results of MLA tk assay with 3 synthetic chemicals in L5178Y cells in vitro, we may provide the important clues on the genotoxic potentials of these 3 chemicals.
Keywords: TRIFLUOROTHYMIDINE-RESISTANT; GLYCEROL CHLOROHYDRINES; CELLS; MUTAGENICITY; DERIVATIVES; DICHLOROPROPANOL; GENOTOXICITY; CARCINOGENS; MUTATIONS; CULTURES